The Major Chromosome Condensation Factors Smc, HBsu, and Gyrase in Bacillus subtilis Operate via Strikingly Different Patterns of Motion - Schibany, Sonja (mSphere, 2020)
Although DNA-compacting proteins have been extensively characterized in vitro, knowledge of their DNA binding dynamics in vivo is greatly lacking. We have employed single-molecule tracking to characterize the motion of the three major chromosome compaction factors in Bacillus subtilis, Smc (structural maintenance of chromosomes) proteins, topoisomerase DNA gyrase, and histone-like protein HBsu. We show that these three proteins display strikingly different patterns of interaction with DNA; while Smc displays two mobility fractions, one static and one moving through the chromosome in a constrained manner, gyrase operates as a single slow-mobility fraction, suggesting that all gyrase molecules are catalytically actively engaged in DNA binding. Conversely, bacterial histone-like protein HBsu moves through the nucleoid as a larger, slow-mobility fraction and a smaller, high-mobility fraction, with both fractions having relatively short dwell times. Turnover within the SMC complex that makes up the static fraction is shown to be important for its function in chromosome compaction. Our report reveals that chromosome compaction in bacteria can occur via fast, transient interactions in vivo, avoiding clashes with RNA and DNA polymerases. IMPORTANCE All types of cells need to compact their chromosomes containing their genomic information several-thousand-fold in order to fit into the cell. In eukaryotes, histones achieve a major degree of compaction and bind very tightly to DNA such that they need to be actively removed to allow access of polymerases to the DNA. Bacteria have evolved a basic, highly dynamic system of DNA compaction, accommodating rapid adaptability to changes in environmental conditions. We show that the Bacillus subtilis histone-like protein HBsu exchanges on DNA on a millisecond scale and moves through the entire nucleoid containing the genome as a slow-mobility fraction and a dynamic fraction, both having short dwell times. Thus, HBsu achieves compaction via short and transient DNA binding, thereby allowing rapid access of DNA replication or transcription factors to DNA. Topoisomerase gyrase and B. subtilis Smc show different interactions with DNA in vivo, displaying continuous loading or unloading from DNA, or using two fractions, one moving through the genome and one statically bound on a time scale of minutes, respectively, revealing three different modes of DNA compaction in vivo.